Discovery of novel N-hydroxy-2-arylisoindoline-4-carboxamides as potent and selective inhibitors of HDAC11. Issue 12 (1st July 2018) - Martin, Matthew W.; Lee, Jennifer Y.; Lancia, David R.; Ng, Pui Yee; Han, Bingsong; Thomason, Jennifer R.; Lynes, Maureen S.; Marshall, C. Gary; Conti, Chiara; Collis, Alan; Morales, Monica Alvarez; Doshi, Kshama; et al.
Graphical abstract: Highlights: Identified novel, potent, and selective first-in-class inhibitors of HDAC11. Synthesis and structure activity relationships of compounds are reported. FT895 displays promising cellular activity and pharmacokinetic properties. FT895 is a valuable tool for further study of the biology of HDAC11. Abstract: N -Hydroxy-2-arylisoindoline-4-carboxamides are potent and selective inhibitors of HDAC11. The discovery, synthesis, and structure activity relationships of this novel series of inhibitors are reported. An advanced analog (FT895 ) displays promising cellular activity and pharmacokinetic properties that make it a useful tool to study the biology of HDAC11 and its potential use as a therapeutic target for oncology and inflammation indications.